Passions of a New Eve (A Contextual Reading of Jeanette Winterson's 'The Passion') - Jukić-Gregurić, Tatjana (Array, 1997)
Jeanette Winterson is one of the most interesting contemporary British writers. Her novel 'The Passion' (1987) is probably the best illustration of her poetics. However, not only does this novel reveal her authorial idiosyncrasies, often anchored in radical feminism, but is also a brilliant dialogue with all the prominent tendencies of contemporary British fiction. The aim of the author is to analyze the relationship between Winterson's textual strategies - characteristic of the literature of the Nineties - and more than two decades of the overall postmodernist background behind her fiction (neohistoricism, magic realism, women's writing). A contextual reading of 'Passion' can thus be seen as an outline of the changes that the British literary scene has undergone since the appearance of 'The French Lieutenant's Woman' (as the first British postmodernist success) in 1969.